Perceptions of tax officers on factors that influence the automatic exchange of information effectiveness to combat tax evasion in Malaysia - Mohamad Zaki, Mohamad Roslani (2023)
Cross-border tax evasion is a growing global problem and has become the main agenda of the Organization for Economic Co-operation and Development with the introduction of financial information sharing initiatives through the Automatic Exchange of Information (AEoI) platform. This study aims to gain the perception of tax officers on the factors that influence the effectiveness of AEoI in combating tax evasion in Malaysia. This study examines three independent variables, namely tax officers’ competency, data quality, and tax policy coordination as factors that influence the effectiveness of AEoI in the fight against tax evasion. Three hypotheses were developed to reflect the expected relationship between the independent and dependent variables. Questionnaire was used as an instrument for data collection in this quantitative research. A total of 220 tax officers who involve in the review of AEoI cases in Johor, Selangor, Kuala Lumpur and Putrajaya were selected as sample. Out of the total questionnaire distributed, 142 responded which represent 64.54% response rate. Primary data was analysed and presented descriptively in the form of percentages, tables, and statistical figures to facilitate the interpretation of data analysis results. The findings show that only tax officers’ competency and data quality have a significant relationship with the effectiveness of AEoI in combating tax evasion. While tax policy coordination shows insignificant relationship. Therefore, it is concluded that the perception of tax officers on their competency and quality of the received data could help improve the effectiveness of AEoI in combating tax evasion in Malaysia but not so for tax policy coordination. Despite its limitations, this study could be considered as the first attempt related to the effectiveness of AEoI which may spark for further research in various aspects of AEoI in the future particularly in the Malaysian context